Penerapan Konseling Individu dengan Teknik Role Reversal untuk Mengatasi Sibling Rivalry dalam Keluarga - Auliasuri, Aninda; Rasmanah, Manah; Sahendra, Yani (Journal of Society Counseling, 2024)
This research is entitled "Application of Individual Counseling Using Role Reversal Techniques to Overcome Sibling Rivalry in the Family". Sibling rivalry is a form of competition, jealousy, and envy between siblings. Client "Ea" considers his younger sibling to be a rival for his father's attention and love, therefore client "Ea" finds it difficult to get along with his younger sibling. This research was conducted to describe the picture of sibling rivalry in "Ea" clients and determine the application of individual counseling using the Role Reversal technique to overcome sibling rivalry in Ea clients in Kapitan Village, Suka Merindu District, Lahat Regency, South Sumatra Province. This research uses a qualitative approach with field research. The subject in this research is the client "Ea". The data collection techniques used are observation, interviews, and documentation. Meanwhile, the data analysis techniques used are pattern matching, making explanations, and time series analysis. The results of the research show that the description of sibling rivalry experienced by client "Ea" contains several aspects, including conflict, jealousy, and resentment. The factors that cause sibling rivalry to occur in "Ea" clients are parental attitudes, gender, type of discipline, birth order, age difference, number of siblings, and influence of other people or outside. In the application of individual counseling using the role reversal technique, five meetings were held with three stages, namely the initial stage, the middle stage or work stage, and the final stage. Overcoming sibling rivalry using the role reversal technique is a process of role reversal or role exchange used by clients who are experiencing anxiety.